2023
DOI: 10.3389/fpsyt.2023.1061284
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating people with schizophrenia from healthy controls in a developing Country: An evaluation of portable functional near infrared spectroscopy (fNIRS) as an adjunct diagnostic tool

Abstract: IntroductionThis study aimed to evaluate portable functional near-infrared spectroscopy (fNIRS) device as an adjunct diagnostic tool in Vietnam to assess hemodynamics when people with schizophrenia and healthy controls performed cognitive tasks.MethodsOne hundred fifty-seven participants were divided into schizophrenia (n = 110) and healthy controls group (n = 47), which were recruited by match of age, and gender. Hemodynamic responses in the frontal cortex were monitored with a 48-channel portable device duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…In recent years, one of the most interesting areas of research is the change in hemodynamic response of the prefrontal cortex as a predictor of response to electroconvulsive treatments [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, one of the most interesting areas of research is the change in hemodynamic response of the prefrontal cortex as a predictor of response to electroconvulsive treatments [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Periáñez et al [9] recently compared the VFT and other tests, including the Stroop test, and suggested that the VFT only significantly correlated with the Stroop color-word (SCWT; Pearson coefficients of r = −0.21) and digit symbol substitution tests in the Wechsler adult intelligence scale (4 th edition; Pearson coefficients of R = 0.22). Moreover, Tran et al [10] recently compared the VFT with the SCWT for the detection of schizophrenia by the change in hemoglobin concentration obtained from fNIRS and showed that the area under the receiver operating characteristic curve of the VFT was higher than that of the SCWT in all regions of interest (ventrolateral PFC, dorsolateral PFC, frontopolar PFC, and orbitofrontal cortex), suggesting that the VFT has higher sensitivity and specificity than the SCWT.…”
Section: Introductionmentioning
confidence: 99%